Novel combination of NB-UVB phototherapy with bFGF-related decapeptide 0.1% and CO2 laser in the treatment of stable, non-segmental vitiligo - Navleen Kaur; Jasleen Kaur; Saurabh Sharma (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Objective: This study aimed to assess the efficacy of a combination therapy involving NB-UVB phototherapy, bFGF-related decapeptide, and fractional CO2 laser in stable non-segmental vitiligo cases. Method: A prospective interventional study was conducted on clinically stable, non-segmental vitiligo patients. The combination therapy was administered for 16 weeks, and patients were followed up for 12 weeks. Data analysis was performed using SPSS version 23.0, with statistical significance set at p < 0.05. Results: Twenty patients aged 12-60 years were enrolled. After 16 weeks, 65% of patients showed good to excellent repigmentation (> 50%) with perifollicular repigmentation being commonly observed. The time for initial repigmentation was as early as 4 weeks. Adverse effects were mild and transient, with no recurrence observed during the follow-up period. Conclusion: This novel combination therapy demonstrated significant repigmentation rates in stable non-segmental vitiligo and presents a potential safe and efficacious therapeutic option in clinical settings.